PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADANG GOLF ADISUTJIPTO YOGYAKARTA - DIAR RESTU IDFIANI (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this research is to find out whether the influence of work motivation affect on employee work discipline that occurred in Padang Golf Adisucipto on the performance of its employees. The number of samples of this study as much 30 employees in Padang Golf Adisutjipto with purposive sampling method. The method of analysis used in this research is multiple regression by performing classical assumption test before getting the best research model. The result of statistical test shows that work motivation variable have positive effect to work discipline to employee performance at Padang Golf Adisucipto.